(untitled) (Medical Forum Monthly, 2024)
Objective: The study was aimed to assess the self-reported competence of dental graduates with basic dental qualification regarding examination of oral and maxillofacial pathologies and provide a comparison of this competence between private and public sector dental graduates of Lahore, Pakistan. Study Design: cross-sectional descriptive study Place and Duration of Study: This study was conducted at the among dental graduates of private sector i.e. University Dental College, The University of Lahore and among public sector graduates i.e. de’ Montmorency College of Dentistry, Lahore from March 2023 to August 2023. Methods: A multi-institutional cross-sectional descriptive study was conducted comprising of dental professionals with basic dental qualification of both private and public sector from March till August 2023.The data was collected through non-probability convenience sampling technique using a self-administered questionnaire which was developed in line with four levels of progression of Miller’s Pyramid. Results: Total of 196 dental professionals participated in the study with females (n=125, 63.80%) and those in the age category of below 30 years (n= 138, 70%) in majority with preponderance of house officers (n=133, 67.9%). Nearly half of the total participants were independent in communicating with the patients and addressing their concerns (n=91, 46.4%). Majority of the participants were able to examine a patient with suspicious oral lesion (n=75, 38.3%) as well as salivary glands and lymph nodes examination (n=66, 33.7%) only under supervision. Mainstream of the participants were only knowledgeable about surgical sieve to assemble a list of differential diagnosis (n=70, 35.7%), Conclusion: The study population was found to be competent in communication skills, history taking and general oral examination. However in the remaining domains, majority of the respondents either merely possessed knowledge or needed supervision to perform the skill.